Safety and efficacy of velaglucerase alfa in Gaucher disease type 1 patients previously treated with imiglucerase. Issue 3 (22nd January 2013) - Zimran, Ari; Pastores, Gregory M.; Tylki‐Szymanska, Anna; Hughes, Derralynn A.; Elstein, Deborah; Mardach, Rebecca; Eng, Christine; Smith, Laurie; Heisel‐Kurth, Margaret; Charrow, Joel; Harmatz, Paul; Fernhoff, Paul; et al.
<x xml:space="preserve">Abstract</x> Velaglucerase alfa is a glucocerebrosidase produced by gene activation technology in a human fibroblast cell line (HT‐1080), and it is indicated as an enzyme replacement therapy (ERT) for the treatment of Gaucher disease type 1 (GD1). This multicenter, open‐label, 12‐month study examined the safety and efficacy of velaglucerase alfa in patients with GD1 previously receiving imiglucerase. Eligible patients, ≥2 years old and clinically stable on imiglucerase therapy, were switched to velaglucerase alfa at a dose equal to their prior imiglucerase dose. Infusion durations were 1 hr every other week. Forty patients received velaglucerase alfa (18 male, 22 female; four previously splenectomized; age range 9–71 years). Velaglucerase alfa was generally well tolerated with most adverse events (AEs) of mild or moderate severity. The three most frequently reported AEs were headache (12 of 40 patients), arthralgia (9 of 40 patients), and nasopharyngitis (8 of 40 patients). No patients developed antibodies to velaglucerase alfa. There was one serious AE considered treatment‐related: a Grade 2 anaphylactoid reaction within 30 min of the first infusion. The patient withdrew; this was the only AE‐related withdrawal. Hemoglobin concentrations, platelet counts, and spleen and liver volumes remained stable through 12 months. In conclusion, adult and pediatric patients with GD1, previously treated with imiglucerase, successfully transitioned to velaglucerase alfa, which was generally well tolerated and demonstrated efficacy over 12 months' treatment consistent with that observed in the velaglucerase alfa Phase 3 clinical trial program. Am. J. Hematol. 88:172–178, 2013. © 2012 Wiley Periodicals, Inc.